Proceso de atención de enfermería en neonato con asfixia perinatal más síndrome de abstinencia. - Pincay Jaen, Kenia Lisbeth (2021)
Perinatal asphyxia, is a preventable disease through changes in risk factors that influence its appearance, this pathology is characterized by the interruption in gas exchange either at the placental or pulmonary level, during or after labor, prolonged exposure to lack of oxygen can lead to a hypercapnic state, hypoxemic to finally end in a neonatal metabolic acidosis, the symptomatic picture with which patients occur are with episodes of apnea, lethargy, bradycardia, hypotension, nasal flaring, changes in body temperature, intercostal pull, cyanosis and in serious state brain and intestinal dysfunction, its diagnosis can be made through a blood gas of the umbilical cord both arterial and venous, assessment according to Apgar and Silverman, which allow to assess the Cardio respiratory status, motor and neurological function, as a treatment has the implementation of supplemental oxygen based on the severity and time of exposure to the lack of oxygen, another measure is the resuscitation of the newborn with cardiac massages and pharmacotherapy with epinephrine at low doses. The present clinical case study revealed a neonate diagnosed with perinatal asphyxia, the purpose of the study was to apply the nursing care process in a patient with perinatal asphyxia plus withdrawal syndrome, the study describes different diagnoses such as exchange impairment gas and nursing care plans and interventions were created based on the needs of the neonate, in addition, a follow-up was provided in the pharmacotherapy prescribed by the treating physician, which helped the recovery of the patient during his hospital stay.